2015
DOI: 10.1590/0102-445071548936077492
|View full text |Cite
|
Sign up to set email alerts
|

How Brazilian learners express modality through verbs and adverbs in their writing: a corpus-based study on n-grams

Abstract: RESUMOCom base na visão de modalidade do arcabouço teórico da sintaxe descritiva, este trabalho analisou um corpus de aprendizes em comparação com um corpus de falantes nativos do inglês com o objetivo de identifi car padrões diferenciados na expressão de valores modais. Para tanto, o estudo concentrou sua análise em n-grams contendo verbos modais e advérbios que expressam modalidade. Essa análise revelou a prevalência dos valores modais epistêmicos em ambos os corpora, bem como a existência de padrões distint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 4 publications
1
6
0
Order By: Relevance
“…Native speakers used obligation/direction and intention/prediction bundles more frequently than the EFL learners. The results are consistent with Tenuta et al (2012) that in their study they also found that native speakers used modals that denote intention/prediction and obligation/direction more frequently than the nonnative speakers.…”
Section: Functions Of Stance Lexical Bundlessupporting
confidence: 92%
“…Native speakers used obligation/direction and intention/prediction bundles more frequently than the EFL learners. The results are consistent with Tenuta et al (2012) that in their study they also found that native speakers used modals that denote intention/prediction and obligation/direction more frequently than the nonnative speakers.…”
Section: Functions Of Stance Lexical Bundlessupporting
confidence: 92%
“…In fact, the use of modals is very common in different genres (see, e.g., Bista, 2009; He & Wang, 2012; Holmes, 1988; Hyland, 1994; Hyland, 1996; Mirahayuni, 2002; Molina, 2012; Moskowich & Crespo, 2019; Nartey & Yankson, 2014; Ngula, 2017; Orta, 2010; Siddique et al, 2019; Tenuta et al, 2015). Since a newspaper editorial is also a significant genre, it also contains modals, for example, the writers of editorials also make use of modals in editorials of world famous newspapers in general (see, e.g., Bonyadi, 2011; Fowler, 2013; Halliday, 1994; Lawal, 2015; Le, 2004; Ntsane, 2015; Qun, 2010; Trajkova, 2011) and Pakistani English newspapers in particular (see, e.g., Hayat & Juliana, 2016; Khalid, 2013; Sadia & Ghani, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Use of modals by editorial writers is also very common (see Bonyadi, 2011; Fowler, 2013; Halliday, 1994; Hayat & Juliana, 2016; Khalid, 2013; Lawal, 2015; Le, 2004; Ntsane, 2015; Qun, 2010; Sadia & Ghani, 2019; Trajkova, 2011). The use of modals in Pakistani English language newspapers is also very common, with the help of which the editorial writers express obligations, probabilities or pass judgements (Halliday, 1994), express beliefs and values (Fowler, 2013), show authorial interest with a particular colour or feel in the story giving an opinion about the truth of the propositions (Simpson, 1993), express necessity as well as possibility (Von Fintel, 2006), influence public opinion, cause the creation of authorial identity in the texts (Molina, 2012), cover the notions of necessity, obligation, permission, possibility, probability and volition (Tenuta et al, 2015), and express attitudes (Sadia & Ghani, 2019) while commenting, informing or reporting about different news events. These modalities which are the focus of the study create stance in the editorials due to which the editorials become full of personal beliefs as well as values (Fowler, 2013; Iwasaki & Yap, 2015; Orta, 2010) which influence the opinions of the readers, that is, the editorial writers use biased language (Timucin, 2010) about hard-hitting on local as well as national news about economy, health, politics and science (Newman & Levy, 2014 cited in Ricketson & Graham, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations